Folded-slot active tag antenna for 5.8GHz RFID applications - Bhaskar, S.; Singhal, S.; Singh, A.K. (Electromagnetics Academy, 2018)
In this paper, a folded slot active tag antenna for 5.8GHz radio frequency identification (RFID) applications is presented. It consists of an inverted U-shaped monopole radiator fed by a coplanar waveguide (CPW) feed line and extended ground planes. A 10 dB return loss bandwidth of 5.65–6.55 GHz is achieved. The overall volume of the presented antenna is 10.7 × 11 × 1.6mm3. A good agreement between the simulated and measured results is observed. The antenna has an omnidirectional radiation pattern at 5.8GHz which makes it suitable for RFID applications. It has advantages of compact dimensions and wider bandwidth than previously reported structures. © 2018, Electromagnetics Academy. All rights reserved.
Keywords: Folded-Slot; Antenna; RFID; Applications